A dual-functional heterosalt additive enables synergistic interphase-bulk engineering for advanced nickel-rich cathodes - Dongni Zhao; Jing Luo; Zixiang Su; Hongzeng Dou; Jingzuo He; Junwei Zhang; Yanjun Zhao; Xinfang Xu; Peng Wang; Ningshuang Zhang; Xiaoling Cui; Shiyou Li (Chemical Engineering Journal, 2026)

Emerging advanced technologies: Modulation of sensory properties in milk and whey systems – A review - Waris Aziz; Khawaja Muhammad Ali Tayyab; Tahir Mahmood Qureshi; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Trends in Food Science & Technology, 2026)

Hydrolyzed konjac glucomannan retards egg white protein digestion via glycosylation -driven gastric texture and rheology modulation - Lulu Guo; Yicheng Guo; Yating Wu; Shende Hu; Xiaosan Wang; Luping Gu; Cuihua Chang; Junhua Li; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

NearStitch: Robust near-surface image stitching for phenotyping - Yu Wang; Shichao Jin; Jianling Tang; Ke Wang; Shan Xu; Yanjun Su; Qinghua Guo; Dong Jiang; Yanfeng Ding; Frédéric Baret (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Toward climate-adaptive rural morphology: a grid-based micro-mesh framework for quantifying microclimate drivers” [Sustainable Cities and Society 148 (2026) 107617] - Zhixing Li; Yanjun Su; Tsung-Hsien Wang; Mimi Tian (Sustainable Cities and Society, 2026)

Toward climate-adaptive rural morphology: a grid-based micro-mesh framework for quantifying microclimate drivers - Zhixing Li; Yanjun Su; Tsung-Hsien Wang; Mimi Tian (Sustainable Cities and Society, 2026)

pH-Shifting combined with heat treatment regulates the aggregate structure and interfacial functional properties of egg white protein microparticles powder - Yating Wu; Yicheng Guo; Junhua Li; Luping Gu; Yanjun Yang; Cuihua Chang; Yujie Su (Food Research International, 2026)

Bioactive orientin-loaded Janus adhesive hydrogel promotes macrophage polarization and gastric injury repair - Yanqi Li; Yang Su; Huawu Yang; Maoyuan Zhao; Wangshuo Yang; Zhenxing Wang; TongTong Zhang; Jie Chen; Yanjun Liu; Lu Liu; Jinhao Zeng (Chemical Engineering Journal, 2026)

A comprehensive LMUPO research framework: Integrating outdoor urban microclimates into building performance analysis and optimization - Zhixing Li; Yi Yang; Rong Xia; Yanjun Su; Zhuoyang Sun (Building and Environment, 2026)

Egg yolk phospholipid peptides as dual-functional nanocarriers for curcumin: Enhanced hypolipidemic effects and mechanism - Ruyi Zhang; Wenhui Feng; Lili Jiang; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Yi Wang; Junhua Li (Food Research International, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Non-invasive geophysical prediction of deep rock mass UCS in complex geological settings - Muhammad Hasan; Lijun Su; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2026)

Potential mechanism of Lactiflorin in treating ulcerative colitis via modulation of the PI3K/AKT pathway: a study integrating network analysis, bioinformatics analysis, and experimental evidence - Mengjia Zhang; Haotian Li; Ningjuan Yan; Man Meng; Xiaolan Su; Yanjun Liu; Runhua Chen; Jianqin Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nanoplastics induce SH-SY5Y cell damage through oxidative stress and disruption of amino acid metabolism - Tianyi Ma; Yuyang Liu; Jingran Sun; Yanjun Fang; Yonghui Wang; Xiaoli Li; Nan Su; Mingzhu Liu; Zunquan Zhao; Jin Wu; Jialei Bai (Toxicology, 2026)

Harnessing Lactiplantibacillus plantarum LW11: A promising bio-preservative for extending cake shelf life through antifungal metabolites - Xuechun Wang; Zhishuo Zhang; Cuihua Chang; Yujie Su; Luping Gu; Yanjun Yang; Hong Sun; Junhua Li (Food Control, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Earthworm activity and its gut microbiota drive the valorization of municipal sewage sludge by enhancing aggregate stability and phytohormone content - Yunxiang Xu; Jin Wang; Guoxun Su; Yizhao Wu; Jiayi Li; Huaixiang Zhou; Xiaoying Yi; Li Tang; Yanjun Shen; Yinsheng Li; Qi Zhao (Journal of Environmental Chemical Engineering, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Enzyme and thermal induced transition of egg white proteins from dense-globular to random coil triggering uniform microparticle formation - Zhishuo Zhang; Yi Wang; Ruyi Zhang; Xuechun Wang; Junhua Li; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang (Food Research International, 2026)

Egg yolk phospholipid peptide-dihydromyricetin nano-composites: Temperature-driven assembly and evaluation of stability and pharmacokinetics - Yingxin Wei; Jinping Zhang; Wenhui Feng; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

Exploring the potential impact of GPC-enriched egg yolk derivatives on cognitive vitality in aging brains: A preliminary study - Wen Yu; Qing Gao; Yanjun Yang; Cuihua Chang; Wei Hu; Yujie Su; Luping Gu; Junhua Li (Food Bioscience, 2025)

Integrating LCZ framework and ENVI-met simulation for multi-scale assessment of urban thermal characteristics and blue-green infrastructure performance - Zhixing Li; Yanjun Su; Rong Xia; Yujie Pan (Sustainable Cities and Society, 2025)

The soil organic carbon sequestration potential and formation efficiency of China’s temperate grasslands - Lu Yang; Ping Li; Yuntao Wu; Nairsag Jalaid; Weixing Liu; Xiaoqiang Liu; Ziyang Peng; Junsheng Huang; Xiaoxia Zhao; Lubing Jiang; Zhaoyu Peng; Sen Yang; et al. (Science Bulletin, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Light-driven release of 6PPD and formation of 6PPD-Q from tire and road wear particles: Mechanisms and cytotoxicity - Danfeng Zhang; Bo Yin; Wen Zhang; Shiyu Wei; Puxing Zhang; Tianyuan Su; Yanjun Liu; Xiwang Tang; Han Wang; Chengfang Yang; Zhuozhi Ouyang; Guining Lu; et al. (Journal of Hazardous Materials, 2025)

Mechanisms driving spectral properties and their associations with above-ground biomass dynamics in a temperate forest - Pengcheng Jiang; Han He; Zikun Mao; Yanjun Su; Mengxu Zhang; Zhichao Xu; Meihui Zhu; Jin Yin; Hongyi Jiang; Shuai Fang; Xugao Wang (Forest Ecology and Management, 2025)

Effect of egg yolk component and its enzymatic hydrolysate on the flavor and texture of walnut cake - Tingting Tang; Qing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Effects of enzyme treatment on structural characteristics of egg yolk, plasma and granule and their correlation with flavor components - Tingting Tang; Wen Yu; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2025)

SenNet: A dual-branch image semantic segmentation network for wheat senescence evaluation and high-yielding variety screening - Jiaqi Yao; Shichao Jin; Jingrong Zang; Ruinan Zhang; Yu Wang; Yanjun Su; Qinghua Guo; Yanfeng Ding; Dong Jiang (Computers and Electronics in Agriculture, 2025)

Metabolite-derived spectral modelling can differentiate heat and drought stress under hot-dry environments - Wanlu Zhong; K.H. Cheng; Laiyin Zhou; Jiaoping Zhang; Fan Zhang; Guoyang Feng; Xinyu Zhang; Qin Ma; Yanjun Su; Shichao Jin; Hon-Ming Lam; Jin Wu (Remote Sensing of Environment, 2025)

PhenoSR: Enhancing organ-level phenotyping with super-resolution RGB UAV imagery for large-scale field experiments - Ruinan Zhang; Shichao Jin; Yi Wang; Jingrong Zang; Yu Wang; Ruofan Zhao; Yanjun Su; Jin Wu; Xiao Wang; Dong Jiang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Sunlight-driven hydrogen peroxide activation via copper hydroxyphosphate with broad spectrum response for imidacloprid degradation: Mechanism insight and DFT calculation - Haoran Zhang; Jiang Li; Yujiao Liu; Sihao Fu; Tianjie Su; Lingyu Meng; Yunfei Wang; Nian Ma; Guocheng Liu; Qinghua Yan; Yanjun Xin; Shuaishuai Xin (Chemical Engineering Journal, 2025)

OSNet: an oriented instance segmentation network of breeding plot extraction from UAV RGB imagery - Ruinan Zhang; Yuanhao Zhang; Shichao Jin; Jingrong Zang; Ruofan Zhao; Jiaqi Yao; Shaochen Li; Qing Li; Yanjun Su; Jin Wu; Qinghua Guo; Yanfeng Ding; et al. (Computers and Electronics in Agriculture, 2025)

STANet-TLA: leveraging deep learning and prior knowledge for large-scale soybean breeding plot segmentation and high-yielding variety screening from UAV time-series data - Shaochen Li; Yinmeng Song; Ke Wang; Yiqiang Liu; Junhong Xian; Hongshan Wu; Xintong Zhang; Yanjun Su; Jin Wu; Qinghua Guo; Shan Xu; Dong Jiang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Improved assessment of post-fire recovery trajectory of forests in Amazon's protected areas - Qianhan Wu; Calvin K.F. Lee; Jonathan A. Wang; Yingyi Zhao; Guangqin Song; Eduardo Eiji Maeda; Yanjun Su; Alfredo Huete; Alice C. Hughes; Jin Wu (Remote Sensing of Environment, 2025)

Cysteine and dialysis mediated inhibition of dynamic changes in glycosylated egg white protein during storage - Lulu Guo; Wanqiu Zhang; Fan Zhang; Shende Hu; Qianwen Zhao; Cuihua Chang; Junhua Li; Zijian Huang; Luping Gu; Yanjun Yang; Yujie Su (Food Chemistry, 2025)

Preparation, characterization and antimicrobial properties of double lysine-modified chitosan and its preservation ability in chicken meat refrigeration - Bin Dong; Yijie Wang; Lili Han; Guirong Cui; Yanjun Lin; Zhiwei Su; Guozhong Zhao (Food Chemistry, 2025)

Production of lactic acid from corn straw: One step and two step pre-treatment strategies and bioconversion efficiency evaluation - Junqiang Shan; Yanjun Chen; Caice Liang; Tianpeng Chen; Xin Zhang; Qingguo Liu; Su Chen; Wenjun Sun; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Effect of adding different egg yolk oil on the flavor and physicochemical properties of mayonnaise - Xuejing Gao; Tingting Tang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2025)

Production of glycerylphosphorylcholine-enriched defatted egg yolk powder through integrated enzymatic and supercritical CO2 processing - Wen Yu; Luping Gu; Cuihua Chang; Yujie Su; Yi Wang; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

The role of defatted hydrolyzed egg yolk powder in protecting DHA algal oil - Yingxin Wei; Huan Rui; Xuechun Wang; Cuihua Chang; Yi Wang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Chemistry, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Effect of enzymatic hydrolysis on flavor enhancement of yogurt fermented by lactic acid bacteria in egg white - Qing Gao; Ruolin Xu; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Bioscience, 2025)

Emerging role of adaptive immunity in diabetes-induced cognitive impairment: from the periphery to the brain - Genhui Yang; Runtao Su; Jie Bu; Ying Li; Xueling Lin; Jiahui Jin; Yanjun Zhang; Pengwei Zhuang; Hong Guo; Qingsheng Yin (Metabolic Brain Disease, 2025)

L1-Tree: A novel algorithm for constructing 3D tree models and estimating branch architectural traits using terrestrial laser scanning data - Yuhao Feng; Yanjun Su; Jiatong Wang; Jiabo Yan; Xiaotian Qi; Eduardo Eiji Maeda; Matheus Henrique Nunes; Xiaoxia Zhao; Xiaoqiang Liu; Xiaoyong Wu; Chen Yang; Jiamin Pan; et al. (Remote Sensing of Environment, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Characterization of liquid egg yolks hydrolyzed by phospholipase: Structure, thermal stability and emulsification properties - Ruolin Xu; Qing Gao; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Research International, 2024)

Extraction of egg yolk lipids via salt-induced synergistic heat treatment: Fabrication, characterization and flavor analysis - Xuejing Gao; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Effects of non-covalently bound polyphenols/vitamins on the structure and functional characteristics of egg yolk powder - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Development of egg yolk lipoprotein hydrolysate for nano-delivery of curcumin: Structure-function relationship - Lili Jiang; Yanjun Yang; Yujie Su; Cuihua Chang; Luping Gu; Chunfang Liu; Junhua Li (Innovative Food Science & Emerging Technologies, 2024)

Critical analysis of using recycled wax oils in asphalt binder considering exudation effects - Han Liu; Bo Su; Haibo Ding; Yanjun Qiu (Fuel, 2024)

Characterization of wax precipitation in wax-doped asphalt binders by variable-temperature polarized light microscope and improved viscosity algorithm - Hai Yuan; Junhao Liu; Bo Su; Jianmin Ma; Haibo Ding; Yanjun Qiu (Fuel, 2024)

Parametric study of correlation of mainshock-aftershock ground motions based on Copula theory - Ziyan Wang; Xiaojun Li; Su Chen; Lei Fu; Bin Zhang; Xianwei Liu; Yanjun Zhu (Journal of Seismology, 2024)

In vitro antimicrobial activity of the novel antimicrobial peptide mytimacin-4 and its influence on the microbial community and quality of pork during refrigerated storage - Bin Dong; Yijie Wang; Guirong Cui; Yuna Wang; Yanjun Lin; Zhiwei Su; Guozhong Zhao (Food Control, 2024)

Differential effects of egg consumption on fecal lipid metabolism: Insights from C57BL/6J mice under chow diet and high-fat diet - Fan Zhang; Tian Yang; Junhua Li; Luping Gu; Cuihua Chang; Li Yang; Zijian Huang; Yujie Su; Yanjun Yang (Food Bioscience, 2024)

Effects of dietary glycerol monolaurate on growth and digestive performance, lipid metabolism, immune defense and gut microbiota of shrimp (Penaeus vannamei) - Renzhi Liu; Yanjun Ding; Futao Jing; Zhifei Chen; Chen Su; Luqing Pan (Fish & Shellfish Immunology, 2024)

Investigation into the impact of enzyme treatment on the structural characteristics of egg yolk protein and its correlation with flavor constituents - Tingting Tang; Xuejing Gao; Junhua Li; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang (Food Hydrocolloids, 2024)

Development of a novel dual-enzyme modification method for the functionality improvement of egg yolk powder - Huan Rui; Luping Gu; Cuihua Chang; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Lactate coordinated with exercise promoted the browning of inguinal white adipose tissue - Xuefei Chen; Yanjun Li; Jingbo Zhang; Wenhua Huang; Jie Su; Jing Zhang (Journal of Physiology and Biochemistry, 2024)

High-purity H2 production from mixed PVC/PET plastic wastes through tandem hydrothermal depolymerization and aqueous phase reforming - Hongcai Su; Yuheng Wu; Jie Pan; Lingjun Zhu; Shurong Wang; Yanjun Hu (Process Safety and Environmental Protection, 2024)

Attribution of streamflow changes during 1961–2019 in the Upper Yangtze and the Upper Yellow River basins - Shanshan Wen; Buda Su; Jinlong Huang; Yanjun Wang; Simon Treu; Fushuang Jiang; Shan Jiang; Han Jiang (Climatic Change, 2024)

Fabrication of phosphatidylcholine-EGCG nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in a Caco-2 monolayer model - Mengya Zhang; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Chemistry, 2024)

PhenoNet: A two-stage lightweight deep learning framework for real-time wheat phenophase classification - Ruinan Zhang; Shichao Jin; Yuanhao Zhang; Jingrong Zang; Yu Wang; Qing Li; Zhuangzhuang Sun; Xiao Wang; Qin Zhou; Jian Cai; Shan Xu; Yanjun Su; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Effects of cholesterol removal treatment on the flavor and physicochemical properties of hot gel egg yolk - Tingting Tang; Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (Food Chemistry, 2024)

Differences in the gelation, digestibility and release of antioxidant peptides of egg white/yolk in boiled eggs - Min Zhu; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2024)

Will the ‘evapotranspiration paradox’ phenomenon exist across China in the future? - Zhenjie Li; Buda Su; Miaoni Gao; Hui Tao; Shan Jiang; Yu Gong; Yanjun Wang; Jian Zhou; Tong Jiang (International Journal of Climatology, 2023)
The uneven changes in potential evapotranspiration (PET) in response to temperature rise are called the ‘evapotranspiration paradox’ phenomenon, which is expected to intensify further under a warming climate. In this paper, we explored the spatial–temporal changes in the future ‘evapotranspiration paradox’ phenomenon over China and its 10 major river sub‐regions under different climate change scenarios. Thus, this paper uses four global climate model outputs under seven shared socioeconomic pathway‐based scenarios (SSP1‐1.9, SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, SSP4‐3.4, SSP4‐6.0 and SSP5‐8.5) from the sixth phase of the Coupled Model Intercomparison Project (CMIP6). Considering the latest IPCC's 6th Assessment Report (AR6), this research emphasizes the 2021–2040 (near‐term), 2041–2060 (mid‐term) and 2081–2100 (long‐term) periods to anticipate the ‘evapotranspiration paradox’ phenomenon. In this study, PET is estimated based on the modified Penman–Monteith (P‐M) method (considering CO 2 ). Furthermore, the paradox phenomenon in this study is defined considering two pivotal conditions: the surface temperature increases but the evaporation decreases (Type I), and the temperature decreases but the evaporation still tends to increase (Type II). The results show that there were only Type I ‘evapotranspiration paradoxes’ that existed in the historical period, which were dominant especially before the 1990s. Nearly 50% of the areas experienced the Type I ‘evapotranspiration paradox’ phenomenon that occurred during 1975–1994 and 1995–2014. Spatially, it covered 100% of the area of the Southeast River (SER) and the Liaohe River (LR) during 1975–1994 and the area of the SER, the HAR, the HHR and the LR during 1995–2014. In the future, the interdecadal growth rate of PET in China is projected to be the highest under the SSP5‐8.5 and the lowest under the SSP3‐7.0 with spatial variation. Importantly, the largest areas of approximately 36% and 45% with the Type I phenomenon are inclined to occur under the SSP1‐1.9 and SSP4‐6.0, respectively, over the long‐term period (2081–2100). The area with the Type I phenomenon will be less than 20% in the near‐term, and it is less than 12% in the mid‐term period. For the Type II evapotranspiration paradox, the uppermost 45% of the area is expected to experience the Type II phenomenon under SSP1‐1.9 during the mid‐term period, while it is 30% under SSP1‐2.6 during the long‐term period. However, this study's findings provide the scientific basis for formulating adaptation and mitigation strategies to combat ‘evapotranspiration paradox’‐related extremes at regional scales.

Fabrication of egg white protein/phosphatidylcholine-EGCG co-assembled nanoparticles with sustained release in simulated gastrointestinal digestion and their transcellular permeability in Caco-2 cultures - Mengya Zhang; Xuejing Gao; Yujie Su; Junhua Li; Cuihua Chang; Luping Gu; Yanjun Yang (Food Hydrocolloids, 2023)

Importation of a novel Indian Ocean lineage carrying E1-K211E and E2-V264A of Chikungunya Virus in Zhejiang Province, China, in 2019 - Lingxuan Su; Xiuyu Lou; Hao Yan; Zhangnv Yang; Haiyan Mao; Wenwu Yao; Yi Sun; Junhang Pan; Yanjun Zhang (Virus Genes, 2023)
The chikungunya virus (CHIKV) is widespread. In Zhejiang province, China, CHIKV infection is often associated with travelers from tropical and subtropical countries. In the present study, three CHIKV isolates from serum samples of travelers in Zhejiang province in 2019 were sequenced, and phylogenetically analyzed to study their molecular characteristics. Sequence analysis showed that the non-structural protein and the structural protein had 37 and 28 amino acid mutations, respectively; no mutation site was found at the E1-A226 residue, which could increase the adaptability of CHIKV to Aedes albopictus . All three samples carried two mutations, namely, E1-K211E and E2-V264A, which were introduced to Bangladesh around late 2015 and Thailand in early 2017. Phylogenetic analysis revealed that these three CHIKVs were Indian Ocean lineage of the East Africa/Central/South Africa genotype (ECSA) and that the MF773566 strain from Bangladesh (Australia/Bangladesh 2017) had the closest evolutionary relationship. The three CHICKs imported into Zhejiang province in 2019 belonged to the ECSA genotype and had multiple amino acid variation sites. The variation in the three samples provides a certain reference for the subsequent research on CHIKV evolution.

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

Combined effect of heating and enzymatic hydrolysis on the dispersibility and structure properties of egg white powder - Tingting Wang; Cuihua Chang; Wanying Cheng; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Journal of Food Engineering, 2023)

Basement structures exert a crucial influence on the structural configuration of later rift development: Insights from the Shanan and Chengbei sag, Bohai Bay Basin - Yanjun Cheng; Zhiping Wu; Wen Su; Mingming Chen; Jie Zhang; Yuqing Liu; Qingbo Wu (Marine and Petroleum Geology, 2023)

Projected land use changes in the Qinghai-Tibet Plateau at the carbon peak and carbon neutrality targets - Runhong Xu; Peijun Shi; Miaoni Gao; Yanjun Wang; Guojie Wang; Buda Su; Jinlong Huang; Qigen Lin; Tong Jiang (Science China Earth Sciences, 2023)

Thermal gelation and digestion properties of hen egg white: Study on the effect of neutral and alkaline salts addition - Junhua Li; Weijian Zhang; Tingting Tang; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Food Chemistry, 2023)

Influence of selected gums on the foaming properties of egg white powders: Kinetics of foam formation and baking performance - Junhua Li; Jinjing Sun; Cuihua Chang; Luping Gu; Yujie Su; Jiali Zhai; Yanjun Yang (Food Hydrocolloids, 2023)

Foaming properties of dried egg white at different outlet temperatures - Junhua Li; Jinjing Sun; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Journal of Food Engineering, 2023)

Sugar alcohols as cryoprotectants of egg yolk: Inhibiting crystals and interactions - Haosheng Zhu; Junhua Li; Yujie Su; Luping Gu; Cuihua Chang; Yanjun Yang (Journal of Food Engineering, 2023)

Characterization of physical properties, volatile compounds and aroma profiles of different salted egg yolk lipids - Xuejing Gao; Junhua Li; Cuihua Chang; Luping Gu; Wen Xiong; Yujie Su; Yanjun Yang (Food Research International, 2023)

Low-temperature upcycling of PET waste into high-purity H2 fuel in a one-pot hydrothermal system with in situ CO2 capture - Hongcai Su; Tian Li; Shurong Wang; Lingjun Zhu; Yanjun Hu (Journal of Hazardous Materials, 2023)

Mapping China’s planted forests using high resolution imagery and massive amounts of crowdsourced samples - Kai Cheng; Yanjun Su; Hongcan Guan; Shengli Tao; Yu Ren; Tianyu Hu; Keping Ma; Yanhong Tang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Gel properties of soy protein isolate-potato protein-egg white composite gel: Study on rheological properties, microstructure, and digestibility - Yuanqi Lv; Lilan Xu; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Ming Zhang; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2023)

Study of effects of dietary quercetin (Que) on growth performance and disease resistance mechanism of Litopenaeus vannamei - Zhifei Chen; Depeng Fan; Luqing Pan; Chen Su; Yanjun Ding; Mingxiang Lu (Aquaculture, 2023)

Dietary cholesterol enhances osmoregulation, antioxidant defenses and immune response of Litopenaeus vannamei to alleviate the macromolecular damage induced by salinity stress - Chen Su; Jinbao Li; Mengyu Zhang; Luqing Pan; Yuxuan Wang; Yanjun Ding; Zhifei Chen; Mingxiang Lu (Aquaculture, 2023)

Experimental and modeling investigation of freezing characteristic curve of silty clay using TDR - Quanming Xin; Yanjun Su; Yang Cao; Xiaokang She; Zhihui Wang; Xianzhang Ling; Tianhong Yang (Cold Regions Science and Technology, 2023)

Immunomodulatory Function of Egg White Peptides in RAW264.7 Macrophage Cells and Immunosuppressive Mice Induced by Cyclophosphamide - Fan Zhang; Junhua Li; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang (International Journal of Peptide Research and Therapeutics, 2022)

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

The influences of the spatial extent selection for non-landslide samples on statistical-based landslide susceptibility modelling: a case study of Anhui Province in China - Chuhan Wang; Qigen Lin; Leibin Wang; Tong Jiang; Buda Su; Yanjun Wang; Sanjit Kumar Mondal; Jinlong Huang; Ying Wang (Natural Hazards, 2022)

Identification of Benign and Malignant Lung Nodules in CT Images Based on Ensemble Learning Method - Yifei Xu; Shijie Wang; Xiaoqian Sun; Yanjun Yang; Jiaxing Fan; Wenwen Jin; Yingyue Li; Fangchu Su; Weihua Zhang; Qingli Cui; Yanhui Hu; Sheng Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Projection of temperature and precipitation under SSPs-RCPs Scenarios over northwest China - Jiancheng Qin; Buda Su; Hui Tao; Yanjun Wang; Jinlong Huang; Tong Jiang (Frontiers of Earth Science, 2021)

Comprehensive evaluation of hydrological models for climate change impact assessment in the Upper Yangtze River Basin, China - Shanshan Wen; Buda Su; Yanjun Wang; Jianqing Zhai; Hemin Sun; Ziyan Chen; Jinlong Huang; Anqian Wang; Tong Jiang (Climatic Change, 2020)

Application of deep learning in ecological resource research: Theories, methods, and challenges - Qinghua Guo; Shichao Jin; Min Li; Qiuli Yang; Kexin Xu; Yuanzhen Ju; Jing Zhang; Jing Xuan; Jin Liu; Yanjun Su; Qiang Xu; Yu Liu (Science China Earth Sciences, 2020)

Population, urbanization and economic scenarios over the Belt and Road region under the Shared Socioeconomic Pathways - Cheng Jing; Hui Tao; Tong Jiang; Yanjun Wang; Jianqing Zhai; Lige Cao; Buda Su (Journal of Geographical Sciences, 2020)

Spatiotemporal variations of aridity index over the Belt and Road region under the 1.5°C and 2.0°C warming scenarios - Jian Zhou; Tong Jiang; Yanjun Wang; Buda Su; Hui Tao; Jiancheng Qin; Jianqing Zhai (Journal of Geographical Sciences, 2020)

Changes of actual evapotranspiration and its components in the Yangtze River valley during 1980–2014 from satellite assimilation product - Jiao Lu; Guojie Wang; Tiantian Gong; Daniel Fiifi T. Hagan; Yanjun Wang; Tong Jiang; Buda Su (Theoretical and Applied Climatology, 2019)

Impact of COMT haplotypes on functional connectivity density and its association with the gene expression of dopamine receptors - Jie Tang; Yanjun Li; Jiayuan Xu; Wen Qin; Qian Su; Qiang Xu; Bing Liu; Tianzi Jiang; Chunshui Yu (Brain Structure and Function, 2019)

Estimation of economic losses from tropical cyclones in China at 1.5 °C and 2.0 °C warming using the regional climate model COSMO‐CLM - Shanshan Wen; Yanjun Wang; Buda Su; Chao Gao; Xue Chen; Tong Jiang; Hui Tao; Thomas Fischer; Guojie Wang; Jianqing Zhai (International Journal of Climatology, 2019)
Adverse impacts and increasing economic losses from tropical cyclones (TCs) are a major focus in respect to the potential global warming of 1.5 °C or even 2.0 °C. Based on observed meteorological data and county‐scale loss records, loss‐inducing rainfall and wind speed thresholds are identified using the regional climate model CCLM to project future TC events in China. An established damage function is combined with future gross domestic product predictions under five shared socio‐economic pathways. At the 1.5 °C warming level, normalized TC losses will be four times higher than in the reference period (1986–2005). At the 2.0 °C warming level, a sevenfold increase is projected. Relative to the 1.5 °C warming level, TCs will become more frequent under the 2.0 °C scenario, especially along the southeast coast of China. Nearly 0.2–0.5% of the increase in gross domestic product might be offset by TC losses between the 1.5 °C and 2.0 °C warming levels, and the single highest TC loss at 2.0 °C may double that at 1.5 °C, with a larger affected area and more severe rainstorms and wind speeds. Rainfall is attributed more often to TC losses than wind speed. Limiting global warming at 1.5 °C would avoid an estimated increase in TC losses of more than 120 billion CNY annually.

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

Analysis of future drought characteristics in China using the regional climate model CCLM - Jinlong Huang; Jianqing Zhai; Tong Jiang; Yanjun Wang; Xiucang Li; Run Wang; Ming Xiong; Buda Su; Thomas Fischer (Climate Dynamics, 2018)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

An integrated UAV-borne lidar system for 3D habitat mapping in three forest ecosystems across China - Qinghua Guo; Yanjun Su; Tianyu Hu; Xiaoqian Zhao; Fangfang Wu; Yumei Li; Jin Liu; Linhai Chen; Guangcai Xu; Guanghui Lin; Yi Zheng; Yiqiong Lin; et al. (International Journal of Remote Sensing, 2017)

Simulation and projection of climatic changes in the Indus River Basin, using the regional climate model COSMO‐CLM - Jinlong Huang; Yanjun Wang; Thomas Fischer; Buda Su; Xiucang Li; Tong Jiang (International Journal of Climatology, 2017)
In this article, the analysis of simulated and projected climatic changes in the Indus River Basin ( IRB ) is presented. The performance of the regional climate model COSMO‐CLM ( CCLM ) driven by the global circulation model MPI‐ESM‐LR is evaluated on the ability of reproducing temperature, precipitation, and wind pattern for the period 1961–2005. There exist quantitative biases, especially in precipitation pattern, which are associated to the diverse reproduction of the atmospheric circulation by the global circulation model. The overall results show that CCLM is able to satisfyingly capture the dominant spatial characteristics in annual temperature and precipitation time series, including the warming trend, and the seasonal variations. The changes in precipitation and temperature over the IRB are projected for the mid‐ (2046–2065) and late‐21st century (2081–2100). Relative to the baseline period (1986–2005), the average annual temperature will increase during the mid‐ and late‐21st century over the whole basin. Extreme temperature events, i.e. heat waves, are more likely to occur. An increase in summer temperature is also projected especially in the upper IRB , where the persistent increase is likely to cause further melting of glaciers. The annual precipitation will decrease in both the mid‐ and late‐21st century with significant spatial changes. A decrease in the monsoon precipitation is also projected, particularly in the central and southern plains of lower altitudes, which might be highly related to the reduction of wet air from the Indian Ocean and the increment in outflow to the east of the IRB . For winter and spring precipitation, except for the late‐21st century under the representative climate pathway (RCP) 2.6, a decreasing trend is projected, which might be caused by the reduction of water vapour from the west. This will further weaken the availability of water resources in these seasons, especially in the upper IRB of higher altitudes.

Intensity–area–duration analysis of droughts in China 1960–2013 - Jianqing Zhai; Jinlong Huang; Buda Su; Lige Cao; Yanjun Wang; Tong Jiang; Thomas Fischer (Climate Dynamics, 2017)

Spatiotemporal distributions of influential tropical cyclones and associated economic losses in China in 1984–2015 - Yanjun Wang; Shanshan Wen; Xiucang Li; Fischer Thomas; Buda Su; Run Wang; Tong Jiang (Natural Hazards, 2016)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Forest fuel treatment detection using multi-temporal airborne lidar data and high-resolution aerial imagery: a case study in the Sierra Nevada Mountains, California - Yanjun Su; Qinghua Guo; Brandon M. Collins; Danny L. Fry; Tianyu Hu; Maggi Kelly (International Journal of Remote Sensing, 2016)

Comparative genomic approach reveals novel conserved microRNAs in Inner Mongolia cashmere goat skin and longissimus dorsi - Rui Su; Shaoyin Fu; Yanjun Zhang; Ruijun Wang; Yanhong Zhou; Jinquan Li; Wenguang Zhang (Molecular Biology Reports, 2015)

Regeneration of insulin monomers from amyloid fibrils by a NH3/H2O2 two-step method - Rui Liu; Rongxin Su; Yanjun Yu; Wei Qi; Libing Wang; Zhimin He (Biotechnology Letters, 2012)

The geo-pattern of course shifts of the Lower Yellow River - Yingjie Wang; Yanjun Su (Journal of Geographical Sciences, 2011)

Comparative QSAR modeling of antitumor activity of ARC-111 analogues using stepwise MLR, PLS, and ANN techniques - Yanjun Yu; Rongxin Su; Libing Wang; Wei Qi; Zhimin He (Medicinal Chemistry Research, 2010)

RfaB, a galactosyltransferase, contributes to the resistance to detergent and the virulence of Salmonella enterica serovar Enteritidis - Jing Su; Dommo Timbely; Minmin Zhu; Xiaomei Hua; Biao Liu; Yanjun Pang; Hengguan Shen; Jinliang Qi; Yonghua Yang (Medical Microbiology and Immunology, 2009)